The SmartAG Partner: CCAFS East Africa Quarterly Newsletter, April - June 2015 - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
We are pleased to share the ninth issue of the SmartAG Partner- a quarterly newsletter of CCAFS East Africa.